FeS quantum dots embedded in 3D ordered macroporous carbon nanocomposite for high-performance sodium-ion hybrid capacitors. Issue 3 (20th December 2018) - Hu, Xiang; Liu, Yangjie; Chen, Junxiang; Jia, Jingchun; Zhan, Hongbing; Wen, Zhenhai
Abstract : The 3D ordered macroporous structure made of FeS quantum dots homogeneously embedded in a 3D inverse opal-structured carbon matrix was designed for sodium ion capacitors with high energy/power densities. Abstract : Sodium-ion hybrid capacitors (SIHCs) have shown great promise in achieving both high energy density and high power density by virtue of synergizing the merits of batteries and capacitors. However, the lack of favorable anode material with superior sodium-ion storage capability is still a major challenge in the development of high-performance SIHCs. Herein, we report the design and synthesis of a promising sodium-ion storage nanohybrid with FeS quantum dots embedded in three-dimensional (3D) inverse opal (IO)-structured N-doped carbon (3D-IO FeS-QDs@NC). By virtue of the robust 3D conductive architecture, the 3D-IO FeS-QDs@NC nanohybrid exhibits favorable features of excellent electron/ion transport kinetics, superior structural stability, as well as impressive sodium-ion storage capability with high specific capacity, outstanding rate capability, and ultra-long cyclic stability. Such highly desirable sodium storage performance inspired us to study their potential application in SHICs by coupling with commercial activated carbon (AC) as a cathode. The as-developed SHICs can deliver a maximum energy density and power output of 151.8 W h kg −1 and 9280 W kg −1, respectively, and an excellent cycling lifespan with 91% capacity retention after 5000 cycles at 1 A g −1, which holds promise for bridging the performance gap between conventional batteries and capacitors.